Endogenous Mergers in Concentrated Markets - Lars Persson; Henrik Horn (The Research Institute of Industrial Economics (IUI), 1998)
This paper proposes an approach for predicting the pattern of mergers when different mergers are feasible. It generalizes the traditional IO approach, employing ideas on coalition-formation from cooperative game theory. The model suggests that in concentrated markets, mergers are conductive to market structures with large industry profits, and thus points to a conflict between private and social incentives. It is shown how mergers may be undertaken in order to preempt other possible, and socially more desirable, mergers. The model also throws light on the formation of research joint ventures and tariff-jumping foreign direct investment.
Keywords: L13; L41; 330; Endogenous mergers; coalition formation; Fusion; Unternehmenskonzentration; Industrieökonomik; Theorie